VD_FINDINFO Jug / 2015 / 175 vom 6. März 2015 - VD Tribunal cantonal (2015)
CONTRAT D'ENTREPRISE, CONTRAT D'ENTREPRISE TOTALE, MANDAT, HONORAIRES, PRIX DE L'OUVRAGE | 120 CO, 363 CO, 394 CO, 398 al. 1 CO, 62 CO, 63 al. 1 CO